2014
DOI: 10.1111/ene.12552
|View full text |Cite
|
Sign up to set email alerts
|

Infantile and childhood onset PLA2G6‐associated neurodegeneration in a large North African cohort

Abstract: The PLAN-associated phenotypes and the challenges of diagnosing the childhood-onset form are delineated, and a common North African founder mutation is identifed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…PLA2G6-associated neurodegeneration (PLAN) describes neurodegeneration with brain iron accumulation (NBIA) caused by PLA2G6 mutations. In our cohort of North African patients with PLAN [1], we noticed that aspartate aminotransferase (AST) levels were increased in 15/15 patients and lactate dehydrogenase (LDH) in 13/14. These abnormalities were detectable from early stages of disease and persisted with time.…”
mentioning
confidence: 94%
“…PLA2G6-associated neurodegeneration (PLAN) describes neurodegeneration with brain iron accumulation (NBIA) caused by PLA2G6 mutations. In our cohort of North African patients with PLAN [1], we noticed that aspartate aminotransferase (AST) levels were increased in 15/15 patients and lactate dehydrogenase (LDH) in 13/14. These abnormalities were detectable from early stages of disease and persisted with time.…”
mentioning
confidence: 94%
“…Both disorders have been meticulously described in previous studies. [9][10][11][12][13][14][15][16][17][18] Our review focuses on the more recently reported genetic NBIA disorders, providing a detailed and comprehensive analysis of these conditions. Chronologically, gene discovery has led to the identification of FAHN, MPAN, BPAN, and CoPAN as distinct NBIA subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…INAD belongs to the family of PLA2G6-associated neurodegeneration. 1 In a child with infantile neuroregression, the peculiar changes in the brainstem and corpus callosum in the presence of cerebellar atrophy serve as a guide to further genetic testing for this disorder. analysis of the radiologic data, critical review of manuscript, final approval of the version to be published.…”
mentioning
confidence: 99%